Evaluasi Coal Handling Facility (CHF) 2 Untuk Memenuhi Target Penerimaan Produksi Batubara Bulan Maret 2018 Ke Stockpile 2 Di PT. Bukit Asam, Tbk. Tanjung Enim, Sumatera Selatan - Andre Agusli; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2018)
Coal handling activities at Muara Tiga Besar has done with two methods, coal from BWE’s bait will transport by BWE system to temporary stockpile MTB before it toward to reclaim feeder 1 and coal from mining front will transport by dump truck to reclaim feeder 2. Coal from MTB will transport to stockpile 2 by CHF MTB. Coal target production of stockpile 2 on March 2018 are 500.000 ton. Incompleteness of coal production on March 2018 caused by some factors, there are high of hitch hour at CHF’s path on March 2018, low capacity production of coal conveyor-22, and unoptimal setting of reclaim feeder speed. Research Methods used in this thesis is a quantitative research method. Efforts that can be made to achieve production targets in March are like increasing the daily work efficiency of reclaim feeder 1 which was originally 83.33% to be 92.85% so that the total rate of coal receipts that could be received by the coal handling facility 2 experienced an increase from 1,429.4 tons / hour to be 1,606.5 tons / hour. In addition, efforts that can be done are increasing the productivity of bulldozers, monitoring the mining front to avoid transporting rock packs, and synchronizing speed reclaim feeders.Keywords:  Coal handling facility, Coal Mining, Reclaim Feeder, Production, Work Efficiency.